1997
DOI: 10.1084/jem.186.6.825
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a Specific Receptor for the Novel CC Chemokine MIP-3α from Lung Dendritic Cells

Abstract: Dendritic cells are potent antigen-presenting cells involved in the initiation of immune responses. The trafficking of these cells to tissues and lymph nodes is mediated by members of the chemokine family. Recently, a novel CC chemokine known as MIP-3α or liver and activation-regulated chemokine has been identified from the EMBL/GenBank/DDBJ expressed sequence tag database. In the present study, we have shown that the messenger RNA for MIP-3α is expressed predominantly in inflamed and mucosal tissues. MIP-3α p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
200
1
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(213 citation statements)
references
References 55 publications
11
200
1
1
Order By: Relevance
“…MIP-3α might contribute to the attraction of memory T-cells to the grafts [20,21]. Expression of IL-15 in the graft and kidney tissue was constitutive, with no major changes in expression after 8 h or 6 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MIP-3α might contribute to the attraction of memory T-cells to the grafts [20,21]. Expression of IL-15 in the graft and kidney tissue was constitutive, with no major changes in expression after 8 h or 6 days.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high serum levels of IP-10 are seen in Type 1 diabetic patients [18]. MIP-3α is a CC chemokine which attracts memory T-lymphocytes and dendritic cells expressing the CCR6 receptor [19,20,21]. The expression of MIP-3α is up-regulated in psoriatic skin [22], atopic dermatitis [23] and rheumatoid arthritis [24] and MIP-3α is involved in the amplification of local inflammatory responses in the liver [25].…”
mentioning
confidence: 99%
“…Many studies showed that DC could attract T cells by secreting chemokines. 38,39 Our previous study demonstrated that Lptn-DC exhibited enhanced preferential chemotaxis to T cells, and were capable of delivering tumor antigen peptide more efficiently to induce tumor rejection in 3LL Lewis lung carcinoma models. 22,40 Certain human cancers have been found to express TAAs that can be recognized immunologically, such as melanoma antigens, polymorphic epithelial mucin (PEM), HER2/neu protooncogen and so on.…”
Section: Gene Therapymentioning
confidence: 98%
“…However, most chemokine receptors of plasmacytoid DC, in particular those for inflammatory chemokines, are apparently not functional in circulating cells (37). Langerhans cells purified from skin or generated in vitro from CD34 + precursors are characterized by the expression of CCR6, the receptor for CCL20/MIP-3a in addition to the receptors expressed by mono-DC (38). CCR6 interacts also with defensins that have agonist activity for DC (39).…”
Section: Transition From Innate To Adaptive Immunity: Dendritic Cellsmentioning
confidence: 99%